2023
DOI: 10.3390/genes14010173
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Omicron Variant Genomic and Phylogenetic Analysis in Iraqi Kurdistan Region

Abstract: Omicron variants have been classified as Variants of Concern (VOC) by the World Health Organization (WHO) ever since they first emerged as a result of a significant mutation in this variant, which showed to have an impact on transmissibility and virulence of the virus, as evidenced by the ongoing modifications in the SARS-CoV-2 virus. As a global pandemic, the Omicron variant also spread among the Kurdish population. This study aimed to analyze different strains from different cities of the Kurdistan region of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…Many gelation and amino acid substitutions were detected in most of the genome; some are novel. The others were also previously seen in strain from Erbil/ Iraq, belonging to the BA.1-sub-lineage (15). The analysis showed that these novel substitutions in the BA.5.2.1 sub-lineage from the Erbil/ Iraq strain were detected, which are T24I, L264F, T327I, P132H (ORF1a), R392C, A509V, I42V (ORF1b), T112I, A27S, V213G, T376F, D405N, R408S, L452R, F486V (spike), S314R, A398V (nucleocapsid).…”
Section: Genomic Analysis Of Ba521 Strainsupporting
confidence: 62%
“…Many gelation and amino acid substitutions were detected in most of the genome; some are novel. The others were also previously seen in strain from Erbil/ Iraq, belonging to the BA.1-sub-lineage (15). The analysis showed that these novel substitutions in the BA.5.2.1 sub-lineage from the Erbil/ Iraq strain were detected, which are T24I, L264F, T327I, P132H (ORF1a), R392C, A509V, I42V (ORF1b), T112I, A27S, V213G, T376F, D405N, R408S, L452R, F486V (spike), S314R, A398V (nucleocapsid).…”
Section: Genomic Analysis Of Ba521 Strainsupporting
confidence: 62%
“…Baghdad, which has 21.3% of Iraq's population, had 28.2 and 21.1% of nationally reported COVID-19 cases and deaths, respectively (5). By the time of this study, Omicron variants were being seen in Iraq (6). Masking, isolation of cases, limiting public exposure, and hospitalization of seriously affected persons in special hospital wards were approaches widely promoted by authorities.…”
Section: Introductionmentioning
confidence: 97%
“…These spikes latch onto cells in the body by binding to receptors (known as ACE2 receptors) on the cell surface, once attached the virus fuses with the cell and the viral genetic material passes into the cell. Where it is copied creating more viral particles and causing more infection (2)(3)(4). Scientific research has been underway to combat the COVID-19 pandemic in different ways.…”
Section: Introductionmentioning
confidence: 99%